2021
DOI: 10.1152/japplphysiol.00602.2020
|View full text |Cite
|
Sign up to set email alerts
|

Acute preexercise supplementation of combined carnosine and anserine enhances initial maximal power of Wingate tests in humans

Abstract: Classic in vitro experiments (Severin's phenomenon) demonstrated that acute carnosine supplementation may potentiate muscle contractility. However, upon oral ingestion, carnosine is readily degraded in human plasma by the highly active serum carnosinase-1 (CN1). We developed a novel strategy to circumvent CN1 by pre-exercise ingestion of combined carnosine (CARN) and anserine (ANS), the methylated analog with similar biochemical properties but more resistant to CN1. First, in vitro hydrolysis was tested by add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Despite the observed improvements in performance in several studies [ 13 , 15 , 16 ], no differences were found in plasma lactate concentration, pH, bicarbonate concentration, and glutathione as oxidative stress marker. This indicates that the benefits currently can not be attributed to the buffering or antioxidant effect of HCD, which are usually described as their main functions [ 17 ].…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Despite the observed improvements in performance in several studies [ 13 , 15 , 16 ], no differences were found in plasma lactate concentration, pH, bicarbonate concentration, and glutathione as oxidative stress marker. This indicates that the benefits currently can not be attributed to the buffering or antioxidant effect of HCD, which are usually described as their main functions [ 17 ].…”
Section: Introductionmentioning
confidence: 73%
“…Higher doses up to 60 mg.kg −1 BM are still only partially effective in inducing carnosinemia, and can be prone to side-effects like headache [ 11 , 26 ] and were therefore not tested for exercise performance. Addition of ANS to the CAR supplement seems more preferable, as ANS is more resistant to degradation by CN1 [ 10 ] and additionally stabilizes co-ingested CAR by competitive inhibition to CN1 [ 12 , 13 ]. The currently used ratio of 1:1 CAR:ANS seems to be a valid ergogenic approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use has been shown to increase muscle carnosine content [11] and to improve high-intensity endurance performance through the attenuation of muscle fatigue and also the enhancement of post-exercise muscle regeneration [12]. The ergogenic potential of the pre-exercise intake of chicken extracts (containing both carnosine and anserine) has already been tested [11,13]. Suzuki et al [11] showed that CBE, containing 0.4 g carnosine and 1.1 g anserine, enhanced the power output of the latter of two sets of repeated sprints.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al [11] showed that CBE, containing 0.4 g carnosine and 1.1 g anserine, enhanced the power output of the latter of two sets of repeated sprints. Blancquaert et al [13] reported that markers of maximal exercise and muscle power during the initial stage of the Wingate test were significantly improved by pre-exercise 20-25 mg/kg of anserine and carnosine supplementation. So far, little is known on dipeptide intake in combination with intense physical exercise or on their influence on the oxi-inflammatory response [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%